New Locality Records of Testudo graeca (L., 1758) in the Eastern Black Sea Region of Türkiye - Ufuk Bülbül; Bilal Kutrup; Batuhan Kansız (Turkish Journal of Bioscience and Collections)
Objective: The literature does not clearly specify the locations inhabited by the spurthighed tortoise (Testudo graeca) from the eastern Black Sea coast of Türkiye. This study thus aimes to reveal new locality records for T. graeca in Trabzon province. Materials and Methods: Two adult male specimens were caught from the Darıca and Konaklar neighborhoods in the respective Akçaabat and Ortahisar districts. Some of the morphological characteristics of these specimens have been recorded using a digital caliper. After taking morphometric measurements, the tortoises were returned to their habitat. No anesthetic procedure was performed on the turtles. Results: Both the Darıca and Konaklar specimens have five vertebral scutes, 11 pairs of marginal scutes, and four pairs of costal scutes on their carapace. In addition, both specimens were seen to have one undivided supracaudal scute and one nuchal scute on their carapace. The Darıca specimen has a straight carapace length (SCL) of 208.19 mm, and plastron length (PL) of 188.08 mm while the Konaklar specimen has an SCL of 216.33 mm and a PL of 196.28 mm. Conclusion: The study compared its specimens’ the pholidosis and morphometric characteristics and color-pattern features with those of specimens reported in the literature. The morphological features of the Darıca and Konaklar specimens are similar to those for the samples of Testudo graeca ibera in the literature. The study’s findings concluded that the samples of Darıca and Konaklar belong to the T. g. ibera subspecies.